2021
DOI: 10.1039/d0cp05868h
|View full text |Cite
|
Sign up to set email alerts
|

Collision-induced dissociation of xylose and its applications in linkage and anomericity identification

Abstract: Different dehydration barrier heights result in different branching ratio, a simple and fast anomeric configuration identification for xylose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 30 publications
3
23
0
Order By: Relevance
“…[ 18 ] In the MS 2 CID spectra of lithium adducts (Figure 2b), the precursor ion is m/z 187, the product of dehydration is ion m/z 169, and products of cross‐ring dissociation are ions m/z 157 ( 0, 1 A), 127 ( 0, 2 A and 0, 4 X) and 97 ( 0, 3 A and 0, 3 X). In our previous studies of glucose, [ 19 ] galactose, mannose, [ 20 ] and xylose, [ 21 ] we have showed that the relative branching ratios of dehydration to cross‐ring dissociation for the anomer with O1 and O2 atoms in cis configuration are larger than that for the anomer in trans configuration. This dehydration propensity rule can be rationalized from the dissociation mechanism.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 18 ] In the MS 2 CID spectra of lithium adducts (Figure 2b), the precursor ion is m/z 187, the product of dehydration is ion m/z 169, and products of cross‐ring dissociation are ions m/z 157 ( 0, 1 A), 127 ( 0, 2 A and 0, 4 X) and 97 ( 0, 3 A and 0, 3 X). In our previous studies of glucose, [ 19 ] galactose, mannose, [ 20 ] and xylose, [ 21 ] we have showed that the relative branching ratios of dehydration to cross‐ring dissociation for the anomer with O1 and O2 atoms in cis configuration are larger than that for the anomer in trans configuration. This dehydration propensity rule can be rationalized from the dissociation mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…The cross‐ring dissociation mechanisms of aldohexose (glucose, galactose, mannose) and aldopentose (xylose) sodium and lithium adducts have been investigated in our previous studies. [ 19–21 ] Figure 3 shows the cross‐ring dissociation mechanism of aldohexose sodium (or lithium) adducts. The cross‐ring dissociation involves sequential reactions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Identifying the arabinose and ribose structures in these polysaccharides is essential for understanding the corresponding biological processes. Although mass spectrometry is more sensitive than other methods (e.g., nuclear magnetic resonance spectroscopy) for identifying carbohydrate structures, differentiating stereoisomers (e.g., arabinose and ribose), anomericity (α- and β-configuration), and the ring form (furanose and pyranose) remains challenging. , We recently developed a novel mass spectrometry method, on the basis of the dissociation mechanisms, for the identification of linkages, anomericity, and stereoisomers of monosaccharides such as glucose, galactose, and mannose, amino sugars, , and xylose . This method can be used for in situ identification of the monosaccharides produced from oligosaccharides through collision-induced dissociation (CID) inside mass spectrometers.…”
Section: Introductionmentioning
confidence: 99%
“…Except for amino sugars, all monosaccharide sodium adducts and lithium adducts have been found to possess the same major dissociation channels (i.e., dehydration and cross-ring cleavage) and similar dissociation mechanisms. However, only the pyranose forms of these monosaccharides have been studied; no monosaccharides in furanose form have been studied. In this work, we examined the arabinose and ribose isomers through chromatography, CID mass spectra, quantum chemistry calculations, and transition state theory.…”
Section: Introductionmentioning
confidence: 99%